Potensi Hasil Varietas Unggul Baru Padi Gogo Pada Lahan Kering Menunjang Peningkatan Produksi Beras Nasional di Kabupaten Garut - SUJITNO, ENDJANG; KURNIA, KURNIA (Agrotrop : Journal on Agriculture Science; Vol 4 No 2 (2014), 2015)
The Yield Potential of Superior Variety of ‘Gogo’ Paddy on The Dry Land in Garut Regency to Support an increase of Domestic Rice Production. Garut regency has the potential dry land with an area of 34.043 ha planting or 15.42% of the acreage of upland rice in West Java. Development of upland rice, especially in dry land can provide a significant contribution to the improvement of the national rice production if managed properly. However, most of dryland farmers, still use a local varieties in upland rice cultivation, so that the production is still low. The use of new varieties of upland rice as a potential solution to solve the problems. To view the suitability of some new high yielding rice varieties in Garut Regency, has implemented a review of some new varieties of upland rice include Situ Patenggang, Inpago 5, Towuti, and Situ Bagendit. The research method used was a randomized block design with 4 treatments and 7 replications. The study was conducted in 2010-2011 on dry season from December 2010 until March 2011. The results showed that all varieties has the potential to be developed in Garut regency. The productivity showed of each variety were Situ Patenggang 3.83 t/ha, Inpago 5 3.72 t/ha, Situ Bagendit 3.08 t/ha and Towuti 3.01 t/ha. The farming analysis showed that the R/C value of each variety were Situ Patenggang 2.35, Inpago 5 2.28, Situ Bagendit 1.89, and Towuti 1.85.
Keywords: Upland rice; high yielding varieties; productivity, dryland PENDAHULUAN Program peningkatan beras nasional (P2BN) adalah salah